МикроРНК ПРИ СТРЕССЕ У РАСТЕНИЙ (Experimental biology, 2015)
It is considered a data by microRNA participation in the answer of plants to stress factors. It is marked the important role mRNA in regulation of development of plants and in response to various kinds of stress.
Keywords: microRNA